Symmetry conserving configuration mixing calculations of Zr isotopes beyond N = 50 shell closure - Rodríguez Tomás R. (EPJ Web of Conferences)
The symmetry conserving configuration mixing (SCCM) method with the Gogny D1S interaction has been used to study the structure of 90-110Zr even-even isotopes. Calculations include the mixing of particle-number and angular momentum projected intrinsic wave functions that are defined along triaxial quadrupole degrees of freedom. A very good description of the 2+1, 4+1 experimental excitation energies and B(E2) transition probabilities is obtained for N ≥ 60 nuclei, but not for 96−98Zr isotopes, where the large (small) experimental energies (transition probabilities) cannot be reproduced with the present calculations. Finally, shape coexistence and shape mixing is also expected to occur in this isotopic chain.